Shared and unique responses of plants to multiple individual stresses and stress combinations: physiological and molecular mechanisms - Pandey, Prachi; Ramegowda, Venkategowda; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2015)
In field conditions, plants are often simultaneously exposed to multiple biotic and abiotic stresses resulting in substantial yield loss. Plants have evolved various physiological and molecular adaptations to protect themselves under stress combinations. Emerging evidences suggest that plant responses to a combination of stresses are unique from individual stress responses. In addition, plants exhibit shared responses which are common to individual stresses and stress combination. In this review, we provide an update on the current understanding of both unique and shared responses. Specific focus of this review is on heat-drought stress as a major abiotic stress combination and, drought-pathogen and heat-pathogen as examples of abiotic-biotic stress combinations. We also comprehend the current understanding of molecular mechanisms of cross talk in relation to shared and unique molecular responses for plant survival under stress combinations. Thus, the knowledge of shared responses of plants from individual stress studies and stress combinations can be utilized to develop varieties with broad spectrum stress tolerance.